Six memorable years on the Arcetri Hill - Veneziano, Gabriele (Il Colle di Galileo, 2024)
I have tried to recall the most vivid memories I have of the six years I spent as a student in Arcetri, and above all as one of the many “gattini” who, at a key moment in the evolution of the theory of fundamental interactions, had the great luck to learn the tools of the game in such a lively and stimulating environment.